Hypercaloric Cafeteria Diet-Induces Obesity, Dyslipidemia, Insulin Resistance, Inflammation and Oxidative Stress in Wistar Rats - Palma-Jacinto José Antonio; Santiago-Roque Isela; Arroyo-Helguera Omar Elind (Journal of Experimental Life Science)
Obesity is a public health problem associated with oxidative stress, chronic inflammation, and insulin resistance. The present study analyzed the cafeteria diet's effects on obesity, oxidative stress, chronic inflammation, and insulin resistance in Wistar rats. Thirty-five male rats were divided into four groups: 1, control (n=10); 2, cafeteria diet (n=9) during 26 weeks (age relative to human adolescence); 3, control 38 weeks (n=9); 4, cafeteria diet during 38 weeks (n=7) (age relative to human adults). The percentage of total adipose tissue (TAT), body mass index, Lee's index, and insulin sensitivity (QUICKI-HOMA) were calculated, as well as metabolic parameters such as lipid profile, glucose levels, glycosylated hemoglobin, antioxidant and oxidative status, TNF-α, and IL-6. Both rat groups with cafeteria diet increased their weight 45.13±15.73 g and TAT 7.75 ± 0.64 g significantly at 26-week, and 46.7±9.05 g weight and TAT 9.97 ± 0.46 at 38 weeks compared to the control group (p<0.05 and p<0.01, respectively). Total cholesterol, HDL, LDL, triglycerides, glucose, Insulin, TBARS, GSH, and catalase activity levels increased in both 26 and 38-week groups vs. control (p<0.01), and TNF-α only at 26 weeks (p<0.01). In conclusion, the cafeteria diet induces obesity in rats, accompanied by hyperglycemia, dyslipidemia, oxidative stress, inflammation, insulin resistance, and TAT. Induction of obesity with a cafeteria diet could be used to study the mechanisms involved in the genesis of overweight, obesity, and comorbidities to establish intervention strategies to prevent these pathologies during adolescence and adulthood.